Establishment and parasitism efficiency of Trichogramma principium (Sugonyaev et Sorokina) on Helicoverpa armigera (Hb.) infesting cotton in Sudan - E. Abdalla, Tag Elsir; M. Elmustafa, Ahmed; A. Mubarak, Hassan (Gezira Journal of Agricultural Science; Vol 10 No 1 (2012), 2023)
This study was conducted at the Gezira Research Station (GRS) farm during 2010/11 season to verify establishment and parasitism efficiency of Trichogramma principium (Sugonyaev et Sorokina) (Hymenoptera : Trichogrammatidae) in eggs of Helicoverpa armigera (Hb . ) (Lepidoptera : Noctuidae) infesting the Sudanese cotton cultivars "Barac 67B" , "Hamid" , "Burhan" and "Abdin" . Trichogramma was acquired from the Rearing Unit , Agricultural Research Corporation (ARC) , at preimaginal (prepupal) stage , in eggs of the rice moth Corcyra cephalonica (Stainton) (Lepidoptera : Pyralidae) . Depending on numbers of H. armigera eggs / 100 plants , one release was done on each of Barac and Hamid and two on each of Abdin and Burhan . The release rate was 24 , 000 parasitoids /fed , at 7x7m distance between release points and 14-day intervals . Evaluation was done between treated plots with Trichogramma versus untreated . Observations consisted of the percentage of emerged parasitoids , percentage of parasitism and the numbers of the African bollworm larvae /100 plants . At the first release , the percentage of emerged parasitoids ranged between 71% in Barac and 86 . 4% in Hamid ; the cultivars` average ranged between 60 . 5% and 94 . 8% and the overall average was 79 . 2% . The percentage of parasitized H. armigera eggs ranged between 22 . 2% and 60% . At the second release , the percentage of emerged adults ranged between 73 . 2% in Burhan and 82 . 1% in Abdin ; the cultivars average ranged between 46 . 6 and 96 . 7% and the overall average was 77 . 7% . The percentage of parasitized H. armigera eggs ranged between 22 . 2% and 77 . 7% . The high level of parasitoid emergence declared a good viability of the released material , tolerance of the parasitoid to the local weather conditions and acceptance of the crop . The levels of parasitism reported were quite acceptable for this introductory release and first occurrence of the parasitoid in this new cotton agroecosysytem . A positive signal of migration from treated to untreated plots was observed through parasitized H. armigera eggs detected in the latter plots . The numbers of H. armigera larvae were negligible in both treatments . Accordingly , for proving potential capacity of establishment and parasitism efficiency against H. armigera , T. principium is strongly recommended for use on Sudanese cotton cultivars .   المقدرة على الاستيطان والكفاءة التطفلية ل   Trichogramma principium (Sugonyaev et Sorokina)  ضد Helicoverpa armigera (Hb.)    على القطن في السودان      أجريت هذه الدراسة بمزرعة محطة بحوث الجزيرة في موسم 2010-2011 للتثبت من المقدرة على  الاستيطان و الكفاءة التطفلية ل  Trichogramma principium (Sugonyaev et Sorokina) (Hymenoptera : Trichogrammatidae) على بيض دودة اللوز الأفريقية Helicoverpa armigera (Hb.) (Lepidoptera : Noctuidae) على أصناف الأقطان السودانية "باراك B 67" ، "حامد" ، "برهان" ، و"عابدين" . تم الحصول على طفيل التريخوجراما من وحدة الإكثار بهيئة البحوث الزراعية في طور ماقبل التشرنق بداخل بيض فراشة الأرز  Corcyra cephalonica (Lepidoptera : Pyralidae) . اعتمادا على عدد بيض دودة اللوز / 100 نبات، فلقد أجريت إطلاقه واحدة على كل من الصنفين باراك و حامد و اطلاقتان على كل من الصنفين عابدين و برهان بمعدل 24000 طفيل للفدان و على مسافات 7x7م بين نقاط الإطلاق و بفاصل 14 يوما بين الإطلاقات. تمت المقارنة بين الحقل المعامل بالتريخوجراما و الغير معامل . اشتمل التقييم على تحديد النسبة المئوية لبزوغ الأطوار المكتملة من الطفيل ، النسبة المئوية للتطفل و عدد اليرقات في ال 100 نبات . عند الإطلاقة الأولى ،   تراوحت النسبة المئوية لبزوغ الأطوار المكتملة بين 71% كما في باراك و 86 . 4% كما في حامد ، و المتوسط  للأصناف بين 60 . 5% و 94 . 8% و المتوسط العام لهم 79 . 2 % و تراوحت النسبة المئوية للتطفل بين 60% و 22 . 2% . عند الإطلاقة الثانية ،   تراوحت النسبة المئوية لبزوغ الأطوار المكتملة بين 73 . 2%% كما في برهان و 82 . 1% كما في عابدين ، و المتوسط للأصناف بين 46 . 6%  و 96 . 7% و المتوسط العام لهم 77 . 7% ، و تراوحت النسبة المئوية للتطفل بين 77 . 7% و 22 . 2% . يدل هذا المستوى العالي من بزوغ الأطوار المكتملة على الحيوية الجيدة للطفيل المطلق ، تحمله للظروف الجويه وتقبله للمحصول العائل .  تعتبر المستويات المتحصل عليها من التطفل مناسبة لهذا الإطلاق الإستهلالى و تواجد الطفيل لأول مرة على  هذا الوسط البيئي الزراعي الجديد للقطن بالسودان . هنالك مؤشرات لبداية هجرة الطفيل من المساحات المعامله لغير المعاملة تمثل في تواجد بيض متطفل علية في الأخيرة . كان عدد يرقات ديدان اللوز قليلا في المعاملتين . و عليه ، و لقابليته على الاستيطان و كفاءته التطفلية المقبولة على ديدان اللوز الأفريقية فان ال T. Principium موصى باستعماله بشدة على أصناف الأقطان السودانية .